Feasibility and Validity of Dementia Assessment by Trained Community Health Workers Based on Clinical Dementia Rating. Issue 7 (3rd June 2013) - Han, Hae‐Ra; Park, So‐Youn; Song, Heejung; Kim, Miyong; Kim, Kim B.; Lee, Hochang Ben
<x xml:space="preserve">Abstract</x> Objectives To determine the level of agreement between dementia rating by trained community health workers (CHWs) based on the Clinical Dementia Rating (CDR) and the criterion standard: physician diagnosis. Design Cross‐sectional validation study. Setting Community gathering places such as ethnic churches, senior centers, low‐income elderly apartments, and ethnic groceries in the Baltimore–Washington metropolitan area. Participants Ninety community‐dwelling Korean‐American individuals aged 60 and older. Measurements The CDR is a standardized clinical dementia staging instrument used to assess cognitive and functional performance using a semistructured interview protocol. Six CHWs trained and certified as CDR raters interviewed and rated study participants. A bilingual geriatric psychiatrist evaluated participants independently for dementia status. Results CHWs rated 61.1% of the participants as having mild cognitive impairment (MCI; CDR = 0.5) or dementia (CDR≥1), versus 56.7% diagnosed by the clinician. A receiver operating characteristic (ROC) curve analysis demonstrated good predictive ability of CDR rating by trained CHWs (area under the ROC curve = 0.86, 95% confidence interval = 0.78–0.93, sensitivity = 85.5%, specificity = 88.6%) in detecting MCI and dementia. Conclusion The findings provide preliminary evidence that trained CHWs can effectively identify community‐dwelling elderly Korean adults with MCI and dementia for early follow‐up assessment and care in a community with scarce bilingual caregivers and programs.